Makna Sajian Makanan Pada Tradisi Pasaji Ponan Menggunakan Teori Interaksi Simbolik - Jannatul Makwa; Vivin Nila Rakhmatullah (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The Samawa tribe is one of the tribes in Indonesia. Each tribe has its own traditions that are different from the others. One of the traditions in Sumbawa is , namely the Pasaji Ponan Culture, has a unique characteristic, namely the snacks that are given in charity at the celebration must be boiled. Meaning that the snacks served cannot be fried. So, the focus of this research is to find out “The Meaning Of Serving Food In The Pasaji Tradition Using Symbolic Interaction Theory”. The mehod used is interpretive qualitative method with the symbolic interaction approach of George Herbert Blumer,s idea. As for informants who selected consisted of 4 (four) types of character characteristics, namely religious leaders, community leaders, traditional leaders and heads of traditional institutions as well as 1 (one) supporting informant from women who were obtained through the purposive sampling technique. There are 2 (two) types of data used, namely primary data and secondary data. Primary data was obtained through in depth interviews technique, while secondary data was obtained through books, journals and other relevant sources. Data were analyzed using the interactive Miles and Huberman method. The results show that the meaning of the snacks presented has a meaning. analyzed using the interactive Miles and Huberman method. The results showed that the meaning of the snacks presented had philosophical meanings including: 1). Serving food as a symbol of plant fertility, 2). Serving food as a medium to strengthen kinship ties, 3). Serving food as a form of prayer. As for the presentation process, namely the snacks are arranged neatly into a tray (stable) and then closed using a serving lid. The snacks consist of 6 (six) types of snacks, namely buras,petikal, lepat,topat,dange, onde-onde and banana with added water drink.